2021
DOI: 10.1038/s41598-021-02716-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple prediction model of hyperuricemia for use in a rural setting

Abstract: Currently, the most widely used screening methods for hyperuricemia (HUA) involves invasive laboratory tests, which are lacking in many rural hospitals in China. This study explored the use of non-invasive physical examinations to construct a simple prediction model for HUA, in order to reduce the economic burden and invasive operations such as blood sampling, and provide some help for the health management of people in poor areas with backward medical resources. Data of 9252 adults from April to June 2017 in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…6,15,19,20 have particular importance in disease prevention and control given their changeable levels developed a prediction model of HUA that contains no invasive tests as predictors, in which BMI was selected as a modifiable risk factor. 21 In addition to the well-known risk factors of HUA, such as overweight/obesity, alcohol consumption, our study found that staying up late was commonly associated with a higher risk of HUA, which is in line with other previous studies. For example, Zou et al found that short sleep is genetically associated with an increased risk of HUA among the white British population.…”
Section: Papersupporting
confidence: 92%
“…6,15,19,20 have particular importance in disease prevention and control given their changeable levels developed a prediction model of HUA that contains no invasive tests as predictors, in which BMI was selected as a modifiable risk factor. 21 In addition to the well-known risk factors of HUA, such as overweight/obesity, alcohol consumption, our study found that staying up late was commonly associated with a higher risk of HUA, which is in line with other previous studies. For example, Zou et al found that short sleep is genetically associated with an increased risk of HUA among the white British population.…”
Section: Papersupporting
confidence: 92%
“…1 ). These variables have also been previously incorporated into models predicting hyperuricemia [ 45 ]. Moreover, these variables had clinical applicability and are routinely measured in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The classification tree model is a tool to represent the processing logic with a binary tree diagram In recent years, scholars have successfully applied the classification tree model to predict COVID-19 in the elderly population, in which the number of sample cases is 41, the same small sample prediction model as this study. 58 In addition, the classification tree has been applied to predict hyperuricemia, 59 predict the survival rate of lung cancer patients, 60 analyze the cause of pediatric pneumonia 61 and other medical and surgical diseases, and its application in medical-related fields has proven its effectiveness. In this study, miR-125b-5p together with miR-155-5p and target genes STAT3 and TRIM32 constituted a classification tree model.…”
Section: Discussionmentioning
confidence: 99%